Örvény . Vortex - Csaba, Szekeres (Hunnia Filmstúdió, 2010)
Verzio FF Duration: 01:15:00 "Vortex" was filmed over a period of six months in the village of Told, on the border with Romania in the north-eastern part of Hungary. It captures the everyday lives of Roma families, their battle to make a living despite the harsh conditions exacerbated by unemployment, poverty, and discrimination. The film focuses on the experiences of three families, their fears of losing their children, and the ever-present challenges of finding enough food to eat and wood to heat their houses. One of the film's protagonists is Juli, who is determined to leave the village at any price. Another family struggles to save their son suffering from cancer, yet another is concerned about their five-year-old who does not talk. Life in the whirlpool of poverty with very little hope of escape.